2005
DOI: 10.1038/sj.onc.1208492
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1-mediated G2/M cell cycle arrest requires ERK1/2 kinase activation

Abstract: Germline mutations in the BRCA1 gene are associated with an increased susceptibility to the development of breast and ovarian cancers. Evidence suggests that BRCA1 protein plays a key role in mediating DNA damage-induced checkpoint responses. Several studies have shown that ectopic expression of BRCA1 in human cells can trigger cellular responses similar to those induced by DNA damage, including G2/M cell cycle arrest and apoptosis. While the effects of ectopic BRCA1 expression on the G2/M transition and apopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
52
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 47 publications
4
52
2
Order By: Relevance
“…In keeping with these results, it was recently shown that BRCA1 destabilized Cdc25C by a mechanism requiring ERK1/2 activation and proteasomal function. 34 Furthermore, our data are reminiscent of a previously described model in which the stability of Cdc25A, another member of the Cdc25 family, is regulated through phosphorylation by CHK1. 41,42 It is presently well-known that phosphorylation of Cdc25C at serine 216 induces 14-3-3 binding, cytosolic retention and further G 2 /M checkpoint in response to DNA damage.…”
Section: Discussionsupporting
confidence: 59%
See 2 more Smart Citations
“…In keeping with these results, it was recently shown that BRCA1 destabilized Cdc25C by a mechanism requiring ERK1/2 activation and proteasomal function. 34 Furthermore, our data are reminiscent of a previously described model in which the stability of Cdc25A, another member of the Cdc25 family, is regulated through phosphorylation by CHK1. 41,42 It is presently well-known that phosphorylation of Cdc25C at serine 216 induces 14-3-3 binding, cytosolic retention and further G 2 /M checkpoint in response to DNA damage.…”
Section: Discussionsupporting
confidence: 59%
“…Downregulation of Cdc25C has been previously reported in response to UVB exposure, 38 γ radiations, 39 BRCA1 expression 34 or infection by adenovirus 40 and related either with a decrease of transcription 39 or a proteasomal degradation. 22,34,40 Interestingly, Singh and colleagues recently proposed that serine 216 could control Cdc25C stability. 22 Consistent with such idea, we demonstrate that phosphorylation at serine 216 by active ERK1/2 targets Cdc25C for ubiquitination and further proteasomal degradation in response to p14 ARF .…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…There is contradictory evidence of a role for MAPK signaling in G 2 and mitosis in mammalian cells (5,6,8), but recent evidence suggests that some of this maybe attributed to cell lineage-dependent differences (44). MAPK signaling has also been implicated in the G 2 arrest associated with overexpression of BRCA1 and p14ARF, although these mechanisms involved Chk1, differentiating them from the present study (45,46).…”
Section: Discussioncontrasting
confidence: 75%
“…In the Ad.dnMEK1 vector, the MEK1 cDNA has been altered and two crucial serine residues located in the catalytic domain (Ser 217 and Ser 221 ) were replaced by alanines. The resulting MEK1 mutant has dominant negative activity and can be used to block the activation of ERK1/2 by wild-type MEK1 as described (30).…”
mentioning
confidence: 99%